Composite oxide loaded bimetallic catalyst as well as preparation method and application thereof

The composite oxide-supported bimetallic catalyst, utilizing Zn-Zr or Zn-Cu composite oxides with Pt and Bi, significantly improves glycerol oxidation efficiency by achieving high conversion and selectivity rates, overcoming the limitations of existing catalysts.

CN119186559APending Publication Date: 2024-12-27SHANDONG CHAMBROAD PETROCHEMICALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411694408.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Current catalysts for glycerol oxidation to produce 1,3-dihydroxyacetone suffer from low conversion rates and selectivity, poor stability, and short lifespan, with existing methods failing to achieve optimal results in terms of activity and selectivity.

Method used

A composite oxide-supported bimetallic catalyst is developed, using Zn-Zr or Zn-Cu composite oxides as carriers with sequentially loaded Pt and Bi, optimized through specific molar ratios and preparation methods like coprecipitation and impregnation, to enhance catalytic performance.

Benefits of technology

The catalyst achieves a high glycerol conversion rate of up to 95.7% and dihydroxyacetone selectivity of up to 91.4%, with ease of separation and recovery, addressing the limitations of previous catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composite oxide loaded bimetallic catalyst as well as a preparation method and application thereof. The composite oxide loaded bimetallic catalyst comprises a carrier, and Pt and Bi which are sequentially loaded on the carrier, the carrier is a Zn-Zr composite oxide or a Zn-Cu composite oxide. According to the invention, Pt and Bi are matched for use, and a bimetallic active site can be formed between Pt and Bi, so that in the subsequent process of preparing DHA through selective oxidation of glycerol, DHA is preferably generated, and the reaction is carried out in the direction of obtaining DHA. Tests show that after the composite oxide loaded bimetallic catalyst provided by the invention is adopted, the catalyst is easy to separate and recover after reaction, and higher glycerol conversion rate (up to 95.7%) and DHA selectivity (up to 91.4%) can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a composite oxide-supported bimetallic catalyst and a preparation method and application thereof. Background Art

[0002] Biodiesel is a clean and low-carbon transportation fuel. It is considered to be a renewable energy source with great development prospects due to its advantages such as easy availability of raw materials, environmental friendliness and renewability, and high safety performance. However, biodiesel produces a large amount of byproduct - glycerol during the production process, which leads to excess glycerol. Therefore, the effective use of excess glycerol byproducts to produce various high value-added chemicals has attracted extensive attention from the international community.

[0003] 1,3-Dihydroxyacetone (DHA), as an important chemical and biochemical raw material, plays an important role in the cosmetics, food, and pharmaceutical industries. At present, DHA is mainly prepared by microbial fermentation. However, the microbial fermentation method has the disadvantages of low reaction substrate concentration, low yield of target products, long fermentation cycle, and high cost of product separation and purification. Therefore, researchers generally began to pay attention to a method for preparing DHA by direct catalytic oxidation of glycerol with high yield, low cost, green environmental protection, mild conditions, and simple separation. At present, using relatively cheap oxygen as an oxidant combined with a catalyst to carry out glycerol oxidation reaction is an environmentally friendly and low-cost solution. In addition, by regulating the catalyst and reaction conditions, glycerol can be selectively oxidized to obtain products with higher added value, especially products with high market demand such as dihydroxyacetone, lactic acid, and glyceric acid. Therefore, the selective oxidation of glycerol has gradually become a hot spot for glycerol conversion.

[0004] CN101279902A discloses a Pt / C catalyst for oxidizing glycerol to obtain dihydroxyacetone. The reaction is carried out at 60°C for 6 hours, and a glycerol conversion rate of 53.38% can be achieved. However, the weight yield of dihydroxyacetone is low, only 3.42wt%.

[0005] CN102432445A discloses a method for preparing DHA by selectively oxidizing glycerol using hydrogen peroxide, but the selectivity of DHA in this method is still low, reaching only 24.2-85.7%. Hu et al. reported that a fixed bed reactor was used to oxidize glycerol with a Pt-Bi / C catalyst at 80°C and acidic conditions, wherein the glycerol conversion rate was 80% and the 1,3-dihydroxyacetone selectivity was 48%.

[0006] CN105439831A discloses a method for producing 1,3-dihydroxyacetone by catalytic oxidation of glycerol using a supported gold catalyst (ZnO, copper-aluminum hydrotalcite, spinel as a carrier). Under high pressure conditions, Au / spinel can achieve a selectivity of 94.8% for dihydroxyacetone, but the conversion rate of glycerol is only 21.6%.

[0007] It can be seen that the current catalysts still have a lot of room for improvement in the activity and selectivity of glycerol oxidation. In addition, the catalysts have poor stability, short life and relatively poor activity during the reaction. Summary of the invention

[0008] In view of this, the object of the present invention is to provide a composite oxide-supported bimetallic catalyst and a preparation method and application thereof. The composite oxide-supported bimetallic catalyst has a high glycerol conversion rate and dihydroxyacetone selectivity.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a composite oxide-supported bimetallic catalyst, comprising a carrier and Pt and Bi sequentially supported on the carrier;

[0011] The carrier is a Zn-Zr composite oxide or a Zn-Cu composite oxide; the carrier is in the form of powder;

[0012] In the composite oxide-supported bimetallic catalyst, the mass percentage of Bi is 0.5-3%; the mass percentage of Pt is 1.5-5%.

[0013] Preferably, in the composite oxide-supported bimetallic catalyst, the mass percentage of Bi is 0.5-1.5%; the mass percentage of Pt is 2.5-4%.

[0014] Preferably, in the Zn-Zr composite oxide, the molar ratio of Zn to Zr is (2-10):(0.5-5).

[0015] Preferably, in the Zn-Cu composite oxide, the molar ratio of Zn to Cu is (1-6):(0.1-3).

[0016] Preferably, the Zn—Zr composite oxide or Zn—Cu composite oxide is in the form of powder.

[0017] In a second aspect, the present invention provides a method for preparing the composite oxide-supported bimetallic catalyst, comprising the following steps:

[0018] S1: providing a Zn source, a Zr source and a Cu source, obtaining precipitates of the Zn source, the Zr source or the Zn source and the Cu source respectively through a coprecipitation reaction, and then calcining to obtain a Zn-Zr composite oxide or a Zn-Cu composite oxide;

[0019] S2: loading a Pt source onto the Zn-Zr composite oxide or Zn-Cu composite oxide by an impregnation method, and then calcining the mixture to obtain a catalyst precursor loaded with Pt;

[0020] S3: The catalyst precursor loaded with Pt is mixed with a Bi source, calcined, and activated to obtain a composite oxide-loaded bimetallic catalyst.

[0021] Preferably, the co-precipitation method uses an alkaline precipitant.

[0022] Preferably, the alkaline precipitant is selected from any one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate.

[0023] Preferably, the coprecipitation method is carried out at a pH of 9 to 11.

[0024] Preferably, the calcination temperature in step S1 is 300-800° C. and the calcination time is 2-10 hours.

[0025] Preferably, the temperature of the impregnation method is 30-50° C., and the time is 3-5 hours; the impregnation method adopts an equal volume impregnation method or an excess impregnation method.

[0026] Preferably, the calcination temperature in step S2 is 400-700° C. and the calcination time is 3-8 hours.

[0027] Preferably, the calcination temperature in step S3 is 300-600° C. and the calcination time is 3-8 hours.

[0028] Preferably, the Zn source is selected from any one or more of zinc nitrate, zinc chloride or zinc sulfate.

[0029] Preferably, the Zr source is selected from any one or more of zirconium chloride, zirconium nitrate or zirconium sulfate.

[0030] Preferably, the Cu source is selected from copper nitrate and / or copper chloride.

[0031] Preferably, the Pt source is selected from platinum chloride and / or chloroplatinic acid.

[0032] Preferably, the Bi source is selected from any one or more of bismuth nitrate, bismuth chloride or bismuth acetate.

[0033] In a third aspect, the present invention provides an application of the above-mentioned composite oxide-supported bimetallic catalyst in the selective oxidation of glycerol to prepare 1,3-dihydroxyacetone.

[0034] In a fourth aspect, the present invention provides a method for preparing 1,3-dihydroxyacetone by selective oxidation of glycerol, comprising the following steps:

[0035] The glycerol aqueous solution is mixed with a catalyst and reacted in the presence of oxygen to obtain 1,3-dihydroxyacetone;

[0036] The molar ratio of glycerol to catalyst in the glycerol aqueous solution is (3-11):(0.1-4.0);

[0037] The catalyst is the composite oxide-supported bimetallic catalyst involved in the above technical solution.

[0038] In a third aspect, the present invention provides a method in which the reaction temperature is 100-250°C and the reaction time is 2-6 hours.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention provides a composite oxide-supported bimetallic catalyst, which uses Zn-Zr composite oxide and / or Zn-Cu composite oxide as a carrier, and can make the prepared catalyst activity better than that of a single carrier.

[0041] Specifically, the present invention sequentially loads Pt and Bi on the above-mentioned Zn-Zr composite oxide or Zn-Cu composite oxide carrier as catalytic active components, which can be stably adsorbed on the above-mentioned carrier and have very high dispersibility. The present invention uses Pt and Bi in combination, and a bimetallic active site can be formed between the two. In the subsequent selective oxidation process of glycerol to prepare DHA, it is beneficial to preferentially generate DHA and facilitate the reaction to proceed in the direction of obtaining DHA.

[0042] According to tests, the composite oxide-supported bimetallic catalyst provided by the present invention is not only easy to separate and recover the catalyst after the reaction, but also can obtain a higher glycerol conversion rate (up to 95.7%) and DHA selectivity (up to 91.4%). DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In view of the fact that the oxidation activity and selectivity of glycerol catalyzed by the catalysts in the prior art still have much room for improvement and enhancement, the present invention provides a composite oxide-supported bimetallic catalyst, comprising a carrier and Pt and Bi sequentially supported on the carrier.

[0045] In the present invention, the carrier is a Zn-Zr composite oxide or a Zn-Cu composite oxide. The present invention uses the above composite oxide as a carrier because the activity of the prepared catalyst is better than that of the catalyst of a single carrier. It should be noted that in the Zn-Zr composite oxide or the Zn-Cu composite oxide, the molar ratio of Zn to Zr and the molar ratio of Zn to Cu will affect the catalyst activity. Therefore, the present invention preferably has a molar ratio of Zn to Zr in the Zn-Zr composite oxide of (2~10):(0.5~5), preferably (5~7):(2.5~4); in the Zn-Cu composite oxide, the molar ratio of Zn to Cu is (1~6):(0.1~3), preferably (2.5~4):(0.5~2).

[0046] According to research, the present invention has found that after the carrier, i.e., Zn-Zr composite oxide or Zn-Cu composite oxide, is pressed into tablets, the catalytic activity and selectivity of the catalyst finally obtained tend to decrease. Therefore, the present invention preferably prefers that the Zn-Zr composite oxide or Zn-Cu composite oxide is in powder form.

[0047] The present invention sequentially loads the catalytic active components: Pt and Bi on the above-mentioned carrier. The present invention uses Pt and Bi in combination, and a bimetallic active site can be formed between the two. The existence of this special structure enables the above-mentioned catalyst to preferentially break the CH bond on the secondary carbon position of glycerol to generate DHA when used for the selective oxidation of glycerol. At the same time, it can further push the reaction in the direction of generating DHA, thereby releasing the bimetallic active site on the catalyst surface and promoting the reaction to proceed to the next step.

[0048] It should be noted that in the present invention, the mass ratio of the carrier, Bi, and Pt needs to be within an appropriate range so that the above-mentioned catalyst has excellent catalytic activity and selectivity. Therefore, after screening and optimization, the present invention calculates the mass percentage of Bi as 100% based on the mass of the composite oxide-supported bimetallic catalyst, and the mass percentage of Bi is 0.5~3%, preferably 0.5~1.5%; the mass percentage of Pt is 1.5~5%, preferably 2.5~4%, and the balance is the carrier.

[0049] The present invention also provides a method for preparing the composite oxide-supported bimetallic catalyst, comprising the following steps:

[0050] S1: providing a Zn source, a Zr source and a Cu source, obtaining precipitates of the Zn source, the Zr source or the Zn source and the Cu source respectively through a coprecipitation reaction, and then calcining to obtain a Zn-Zr composite oxide or a Zn-Cu composite oxide;

[0051] S2: loading a Pt source onto the Zn-Zr composite oxide or Zn-Cu composite oxide by an impregnation method, and then calcining the mixture to obtain a catalyst precursor loaded with Pt;

[0052] S3: The catalyst precursor loaded with Pt is mixed with a Bi source, calcined, and activated to obtain a composite oxide-loaded bimetallic catalyst.

[0053] According to the present invention, firstly, a Zn source, a Zr source and a Cu source are provided. In the present invention, the Zn source is selected from zinc nitrate and / or zinc chloride, preferably zinc nitrate; the Zr source is selected from any one or more of zirconium chloride, zirconium nitrate or zirconium sulfate, preferably zirconium nitrate; the Cu source is selected from copper nitrate and / or copper chloride, preferably copper nitrate. The present invention has no particular restrictions on the sources of the Zn source, the Zr source and the Cu source, and they can be generally commercially available products.

[0054] In some embodiments of the present invention, it is preferred to obtain precipitates of Zn source, Zr source or Zn source, Cu source respectively by coprecipitation reaction, and roast to obtain Zn-Zr composite oxide or Zn-Cu composite oxide. Wherein, the coprecipitation method uses an alkaline precipitant to control the pH to 9-11, preferably 10-11; the alkaline precipitant can be specifically selected from any one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate, preferably ammonia water, and the concentration of the alkaline precipitant is 0.1-1.0 mol / L, preferably 0.3-0.6 mol / L. The roasting conditions include: temperature of 300-800°C, preferably 400-600°C; time of 2-10h, preferably 3-6h.

[0055] For example, in some embodiments of the present invention, a certain proportion of Zn source and Zr source (or Cu source) is weighed and dispersed in a certain amount of deionized water, stirred and dissolved to a clear and transparent solution, and an alkaline precipitant (concentration of 0.1-1.0 mol / L) is added to the above solution, and the pH is controlled at 9-11 to initiate a coprecipitation reaction. Finally, the coprecipitation reaction product is stirred for 0.5-1h, aged for 1-3h, and then the precipitate is taken out and filtered, and the filter cake is washed with a large amount of deionized water until the pH is neutral, and the solid solution is collected after roasting, which is Zn-Zr composite oxide or Zn-Cu composite oxide.

[0056] As a preferred technical solution, the solid solution is preferably ground to obtain a Zn-Zr composite oxide or a Zn-Cu composite oxide in powder form.

[0057] As a preferred technical solution, after washing to neutrality, the filter cake is preferably dried and then calcined. The drying conditions include: temperature of 30-200°C, preferably 80-120°C; time of 1-24h, preferably 4-8h.

[0058] After obtaining the Zn-Zr composite oxide or Zn-Cu composite oxide, according to the present invention, a Pt source is loaded on the Zn-Zr composite oxide or Zn-Cu composite oxide by an impregnation method, and then calcined to obtain a catalyst precursor loaded with Pt.

[0059] In the present invention, the Pt source is selected from platinum chloride and / or chloroplatinic acid, preferably chloroplatinic acid.

[0060] In the present invention, the impregnation method can be performed by an equal volume impregnation method or an excess impregnation method, and the equal volume impregnation method is preferred.

[0061] Illustratively, in some embodiments of the present invention, an equal volume of a Pt source is immersed in the above-mentioned Zn-Zr composite oxide or Zn-Cu composite oxide, immersed at 30-50°C for 3-5 h, preferably at 35-45°C for 3.5-4.5 h, and then dried at 80-100°C, and then the obtained solid product is calcined at 400-700°C for 3-8 h, preferably at 500-600°C for 4-7 h, to obtain a catalyst precursor loaded with Pt.

[0062] Then, according to the present invention, the catalyst precursor loaded with Pt is mixed with a Bi source, calcined, and activated to obtain a composite oxide-loaded bimetallic catalyst. In the present invention, the purpose of the activation is to activate or repair the surface active sites of the catalyst; to change the structure and electrons of the loaded metal and to improve the catalytic performance of the catalyst.

[0063] Illustratively, in some embodiments of the present invention, a bismuth source is uniformly mixed and ground with a catalyst precursor loaded with Pt in a certain proportion, and the resulting solid solution is calcined at 300-600°C for 3-8h, preferably at 400-500°C for 4-6h, and then activated with hydrogen to obtain the composite oxide-loaded bimetallic catalyst.

[0064] In summary, the present invention provides a composite oxide-supported bimetallic catalyst, which is composed of a composite oxide carrier and active components (Pt and Bi). The present invention first adopts a coprecipitation method to obtain a composite oxide carrier, then adopts an impregnation method to load Pt on the composite oxide carrier to obtain a catalyst precursor, and finally adopts a molten salt method to load Bi, calcine, and obtain a composite oxide-supported bimetallic catalyst. It can be seen that the above preparation method provided by the present invention is simple and convenient, easy to implement, and is conducive to industrialization or industrial production.

[0065] The present invention also provides an application of a composite oxide-supported bimetallic catalyst in the selective oxidation of glycerol to prepare 1,3-dihydroxyacetone.

[0066] Specifically, the present invention also provides a method for preparing 1,3-dihydroxyacetone by selective oxidation of glycerol, comprising the following steps:

[0067] The glycerol aqueous solution is mixed with the composite oxide-supported bimetallic catalyst and reacted in the presence of oxygen to obtain 1,3-dihydroxyacetone.

[0068] In the present invention, the molar ratio of glycerol to catalyst in the glycerol aqueous solution is (3-11):(0.1-4.0), preferably (4-8):(0.3-3.0), and more preferably 7:0.5. The reaction temperature is 100-250°C, preferably 150-200°C; the reaction time is 2-6h, preferably 3-4h.

[0069] In some embodiments of the present invention, preferably, a certain amount of 0.1-3 M glycerol aqueous solution is pipetted with a pipette, a certain amount of catalyst is weighed, and both are added to a reaction kettle, wherein the reaction kettle is a high-pressure reaction kettle with a mechanical stirrer and a temperature control system, and after being tightly sealed, N is first introduced. 2 Replace the air in the kettle 3 to 5 times, then introduce O 2 Replace the N in the kettle 2 After 3 to 4 times, add the required O to start the reaction. 2 , adjust the stirring speed of the reactor to 400r / min, heat to the reaction temperature of 100-250℃ within 30-60min, start timing, react for 2-6h, cool the reactor with ice water, remove the residual gas in the reactor and open the reactor, filter the liquid through a needle filter for testing, and recover the catalyst by filtering and washing.

[0070] According to tests, the composite oxide-supported bimetallic catalyst provided by the present invention is not only easy to separate and recover the catalyst after the reaction, but also can obtain a higher glycerol conversion rate (up to 95.7%) and DHA selectivity (up to 91.4%).

[0071] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products. Example 1

[0072] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0073] (1) Preparation of composite carrier: 36.05 g zinc nitrate and 18.61 g zirconium nitrate were dispersed in 300 mL deionized water to prepare mixed solution A, and 160 g ammonia solution (0.1 mmol / mL) was slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 11, and the mixture was aged, filtered, washed with a large amount of water, and the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Zr-O carrier.

[0074] (2) Preparation of catalyst: 4.75 g of chloroplatinic acid was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor, and the obtained solid was calcined at 550° C. for 4 h and activated with hydrogen to obtain a Bi-Pt / Zn-Zr-O catalyst, wherein the Pt content was 4% and the Bi content was 0.5%. Example 2

[0075] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0076] (1) Preparation of composite carrier: 48.48 g zinc chloride and 18.61 g zirconium nitrate were dispersed in 300 mL deionized water to prepare mixed solution A, and 160 g ammonia solution (0.1 mmol / mL) was slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 11, and the mixture was aged, filtered, washed with a large amount of water, and the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Zr-O carrier.

[0077] (2) Preparation of catalyst: 4.75 g of chloroplatinic acid was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor, and the obtained solid was calcined at 550° C. for 4 h and activated with hydrogen to obtain the Bi-Pt / Zn-O catalyst, wherein the Pt content was 4% and the Bi content was 0.5%. Example 3

[0078] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0079] (1) Preparation of composite carrier: 36.05 g zinc nitrate and 10.34 g copper nitrate were dispersed in 300 mL of deionized water to prepare mixed solution A, and 160 g ammonia solution (0.1 mmol / mL) was slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 10, and the mixture was aged, filtered, washed with a large amount of water, and the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Cu-O carrier.

[0080] (2) Preparation of catalyst: 4.75 g of chloroplatinic acid was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor for uniform grinding, and the obtained solid was calcined at 550° C. for 4 h and activated with hydrogen to obtain the Bi-Pt / Zn-Cu-O catalyst, wherein the Pt content was 4% and the Bi content was 0.5%. Example 4

[0081] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0082] (1) Preparation of composite carrier: 36.05 g zinc nitrate and 18.61 g zirconium nitrate were dispersed in 300 mL deionized water to prepare mixed solution A, and 160 g ammonia solution (0.1 mmol / mL) was slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 11, and the mixture was aged, filtered, washed with a large amount of water, and the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Zr-O carrier.

[0083] (2) Preparation of catalyst: 4.75 g of chloroplatinic acid was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.82 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor for uniform grinding, the obtained solid was calcined at 550° C. for 4 h, and activated with hydrogen to obtain the Bi-Pt / Zn-Zr-O catalyst, wherein the Pt content was 4% and the Bi content was 1%. Example 5

[0084] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0085] (1) Preparation of composite carrier: 36.05 g zinc nitrate and 18.61 g zirconium nitrate were dispersed in 300 mL deionized water to prepare mixed solution A, 26.8 g sodium carbonate was dissolved in 180 mL deionized water and slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 9, aged, filtered, washed with a large amount of water, the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Zr-O carrier.

[0086] (2) Preparation of catalyst: 4.75 g of chloroplatinic acid was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor for uniform grinding. The obtained solid was calcined at 550° C. for 4 h and activated with hydrogen to obtain the Bi-Pt / Zn-Zr-O catalyst, wherein the Pt content was 4% and the Bi content was 0.5%. Example 6

[0087] The present invention provides a composite oxide-supported bimetallic catalyst, and a preparation method thereof comprises the following steps:

[0088] (1) Preparation of composite carrier: 36.05 g zinc nitrate and 18.61 g zirconium nitrate were dispersed in 300 mL deionized water to prepare mixed solution A, and 160 g ammonia solution (0.1 mmol / mL) was slowly added dropwise to the mixed solution A to cause a coprecipitation reaction. The pH of the system was controlled at 11, and the mixture was aged, filtered, washed with a large amount of water, and the filter cake was fully dried at 60°C overnight, calcined at 650°C for 4 h in an air atmosphere, cooled naturally, and ground into powder to obtain a composite Zn-Zr-O carrier.

[0089] (2) Preparation of catalyst: 5.05 g of platinum powder dissolved in aqua regia was impregnated into 13.85 g of the composite carrier prepared in step (1), impregnated at 40° C. for 4 h and then dried at 80° C. The obtained solid product was calcined at 550° C. for 4 h and ground to obtain a catalyst precursor. Then 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the catalyst precursor, and the obtained solid was calcined at 550° C. for 4 h and activated with hydrogen to obtain the Bi-Pt / Zn-Zr-O catalyst, wherein the Pt content was 4% and the Bi content was 0.5%. Example 7

[0090] Compared with Example 1, the only difference is that the mass of chloroplatinic acid is 2.38 g, the mass of bismuth nitrate is 1.02 g, the Pt content in the obtained catalyst is 2%, and the Bi content is 0.5%. The remaining preparation steps are the same as those in Example 1. Example 8

[0091] Compared with Example 1, the only difference is that the composite Zn-Zr-O carrier obtained in step (1) is subjected to tableting processing, and the remaining preparation steps are the same as those in Example 1. The Pt content in the obtained catalyst is 4%, and the Bi content is 0.5%.

[0092] Comparative Example 1

[0093] Compared with Example 1, the only difference is that bismuth nitrate is not added in the preparation of the catalyst, and the remaining preparation steps are the same as those in Example 1.

[0094] Comparative Example 2

[0095] (1) Preparation of composite carrier: the same as in Example 1;

[0096] (2) Preparation of catalyst: 1.02 g of bismuth nitrate was weighed and mixed with 10.86 g of the composite carrier, and then 4.75 g of chloroplatinic acid was weighed and impregnated into 13.85 g of the catalyst precursor prepared in step (1). After impregnation for 4 h, the mixture was dried at 80° C. The solid product was calcined at 550° C. for 4 h and ground to obtain the Pt-Bi / Zn-Zr-O catalyst.

[0097] Performance Testing

[0098] Glycerol oxidation reaction:

[0099] 10 mL of 100 mM glycerol aqueous solution was measured and added with 88 mg of the catalyst prepared in Examples 1 to 8 or Comparative Examples 1 to 2, and transferred to a 30 mL high-pressure reactor with a stirring speed of 900 rpm. After reaching the set temperature, oxygen at different pressures was introduced, and 1 mL of sample was taken after the reaction was completed. The catalyst was separated by centrifugation.

[0100] Chromatographic analysis of reaction products:

[0101] The reaction liquid product was filtered with a 0.22 μm pore filter and then detected. 20 μL was injected into the column each time. The product was analyzed using an Agilent 1260 high performance liquid chromatograph equipped with an Alltech OA-1000 Organic Acids column and equipped with a diode array detector and a differential detector. The main monitoring wavelengths of the diode array detector were set to 195 and 210 nm. Standard samples were used for qualitative analysis, and the external standard method was used for quantitative analysis.

[0102] After the high-pressure reaction, the gas phase products were sampled with a needle for detection, and 2 µL was injected into the chromatographic column each time. The products were analyzed using a SHIMADZUNexis GC-2030 high-performance gas chromatograph equipped with an SH-Rtx-Wax capillary column and a dielectric barrier discharge plasma detector. Standard samples were used for qualitative analysis, and external standard method was used for quantitative analysis.

[0103] The test results are shown in Table 1 below:

[0104] Table 1

[0105] From the data of the embodiment and comparative example 1 in Table 1, it can be seen that the composite oxide-supported bimetallic catalyst provided by the present invention has higher activity and selectivity in the glycerol oxidation reaction process than the composite oxide-supported single Pt catalyst. From the data of the embodiment and comparative example 2, it can be seen that the loading order of Pt and Bi will affect the performance of the catalyst. From the comparison of Examples 1 to 6 and Examples 7 to 8, it can be seen that the content of Pt in the catalyst and the morphology of the carrier will also affect the performance of the catalyst.

[0106] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite oxide-supported bimetallic catalyst, characterized in that: It includes a carrier and Pt and Bi sequentially loaded on the carrier; The carrier is a Zn-Zr composite oxide or a Zn-Cu composite oxide; In the composite oxide-supported bimetallic catalyst, the mass percentage of Bi is 0.5-3%; the mass percentage of Pt is 1.5-5%.

2. The composite oxide-supported bimetallic catalyst according to claim 1, characterized in that: In the composite oxide-supported bimetallic catalyst, the mass percentage of Bi is 0.5-1.5%; the mass percentage of Pt is 2.5-4%.

3. The composite oxide-supported bimetallic catalyst according to claim 1 or 2, characterized in that: In the Zn-Zr composite oxide, the molar ratio of Zn to Zr is (2-10):(0.5-5); In the Zn-Cu composite oxide, the molar ratio of Zn to Cu is (1-6):(0.1-3); The Zn-Zr composite oxide or Zn-Cu composite oxide exists in the form of powder.

4. A method for preparing a composite oxide-supported bimetallic catalyst as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: providing a Zn source, a Zr source and a Cu source, obtaining precipitates of the Zn source, the Zr source or the Zn source and the Cu source respectively through a coprecipitation reaction, and then calcining to obtain a Zn-Zr composite oxide or a Zn-Cu composite oxide; S2: loading a Pt source onto the Zn-Zr composite oxide or Zn-Cu composite oxide by an impregnation method, and then calcining the mixture to obtain a catalyst precursor loaded with Pt; S3: The catalyst precursor loaded with Pt is mixed with a Bi source, calcined, and activated to obtain a composite oxide-loaded bimetallic catalyst.

5. The preparation method according to claim 4, characterized in that: The coprecipitation method uses an alkaline precipitant; The alkaline precipitant is selected from any one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate; The coprecipitation method is carried out at a pH of 9 to 11; The calcination temperature in step S1 is 300-800° C. and the calcination time is 2-10 hours.

6. The preparation method according to claim 4 or 5, characterized in that: The temperature of the impregnation method is 30-50°C and the time is 3-5 hours; the impregnation method adopts an equal volume impregnation method or an excess impregnation method; The calcination temperature in step S2 is 400-700°C and the calcination time is 3-8h; The calcination temperature in step S3 is 300-600° C. and the calcination time is 3-8 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that The Zn source is selected from any one or more of zinc nitrate / zinc chloride or zinc sulfate; The Zr source is selected from any one or more of zirconium chloride, zirconium nitrate or zirconium sulfate; The Cu source is selected from copper nitrate and / or copper chloride; The Pt source is selected from platinum chloride and / or chloroplatinic acid; The Bi source is selected from any one or more of bismuth nitrate, bismuth chloride or bismuth acetate.

8. Use of the composite oxide-supported bimetallic catalyst according to any one of claims 1 to 3 or the composite oxide-supported bimetallic catalyst prepared according to the preparation method according to any one of claims 4 to 7 in the selective oxidation of glycerol to prepare 1,3-dihydroxyacetone.

9. A method for preparing 1,3-dihydroxyacetone by selective oxidation of glycerol, characterized in that: The following steps are involved: The glycerol aqueous solution is mixed with a catalyst and reacted in the presence of oxygen to obtain 1,3-dihydroxyacetone; The molar ratio of glycerol to catalyst in the glycerol aqueous solution is (3-11):(0.1-4.0); The catalyst is a composite oxide-supported bimetallic catalyst according to any one of claims 1 to 3 or a composite oxide-supported bimetallic catalyst prepared by the preparation method according to any one of claims 4 to 7.

10. The method according to claim 9, characterized in that The reaction temperature is 100-250° C. and the reaction time is 2-6 hours.

Citation Information

Patent Citations

  • One-step method for preparing dihydroxy acetone by dioxygen catalytic oxidation of glycerol

    CN101279902A

  • Method for preparing dihydroxy acetone by selectively oxidizing glycerin with hydrogen peroxide

    CN102432445A

  • Method for producing 1,3-dihydroxyacetone through catalytic oxidation with supported gold catalyst

    CN105439831A